Concurrent estimation of lamivudine, tenofovir disoproxil fumarate, and efavirenz in blended mixture and triple combination tablet formulation by a new stability indicating RP-HPLC method - Ramreddy Godela (Future Journal of Pharmaceutical Sciences, 2021)
Abstract Background An easy, defined, rapid, and accurate reverse phase high-performance liquid chromatography method was developed and subsequently validated for the concurrent estimation of lamivudine, efavirenz, and tenofovir disoproxil fumarate in their pure blend and combined tablet formulation. An efficient and appropriate separation of the three analytes was attained with Zorbax eclipse XDB-Phenyl column, with a mobile phase of methanol: buffer (0.1% v/v formic acid in water) (73:27 v/v) at a flow rate of 1mL/min and isocratic elution by using 260nm as detection wavelength. Equal ratio of acetonitrile and water was used as diluent. Results The retention times of lamivudine, tenofovir disoproxil fumarate, and efavirenz were found at 2.6, 4.4, and 5.9 min respectively. The linear response for lamivudine, tenofovir disoproxil fumarate, and efavirenz was in the range of 15.0–45.0μg/mL, 15.0–45.0μg/mL, and 20.0–60.0 μg/mL respectively. The method validation was done in accordance to ICH guidelines and all validation parameters in compliance with ICH standards. The degradants produced by stress testing were well resolved from the peaks of active analytes, which stipulates the stability-indicating property of the method. Conclusion The method has the ability to separate lamivudine, efavirenz, and tenofovir disoproxil fumarate concurrently in blended powder and their combined tablet. All degradants produced by application of stress conditions were separated with high resolution and determined with good sensitivity that ensures the stability-indicating property of the method. Thus, the projected method has high probability to adopt in the pharmaceutical industrial sector.